A biomechanical evaluation of the combined elevation test. (May 2017) - Allen, Sam; Phillips, Gemma; McCaig, Steve
Abstract: Objectives: To evaluate biomechanically the relationships between the outcome of the Combined Elevation Test, its component joint motions, and thoracic spine angles. Design: Cross-sectional study. Setting: Laboratory. Participants: 18 elite swimmers and triathletes (11 males and 7 females). Main outcome measures: Combined Elevation Test outcome in forehead and chin positions. Individual joint contributions to test outcome. Results: No sex differences were found in test components, or between head positions. Test outcome was greater in the forehead position than the chin position (34.3 cm vs 30.2 cm; p < 0.001). The variables most strongly associated with test outcome were glenohumeral joint flexion (r = 0.86–0.97; p < 0.001), and shoulder retraction (r = 0.75–0.82; p < 0.001). Total thoracic spine angle related strongly to test outcome in females (r = −0.77 to -0.88; p < 0.05), but not in males (r = −0.17 to -0.24; p > 0.05). Conclusions: The Combined Elevation Test is an effective screening tool, measuring upper limb mobility into shoulder flexion and scapula retraction in both sexes, and thoracic extension in women. It is recommended that the test be performed in the forehead position. If a subject performs poorly on the test, follow up assessments are required to identify the impairment location. Highlights: Combined elevation test performance was measured in two head positions in males and females. There were no differences between the sexes in any test component, or between head positions. Test outcome was greater in the forehead position than the chin position. Glenohumeral joint flexion, and shoulder retraction were strongly associated with test outcome. Total thoracic spine angle related strongly to test outcome in females, but not in males.